High plasma resistin associates with severe acute kidney injury in Puumala hantavirus infection. - Paula S Mantula; Tuula K Outinen; Pia Jaatinen; Mari Hämäläinen; Heini Huhtala; Ilkka H Pörsti; Antti Vaheri; Jukka T Mustonen; Satu M Mäkelä (PLoS ONE, 2018)
Background Puumala hantavirus (PUUV) infected patients typically suffer from acute kidney injury (AKI). Adipokines have inflammation modulating functions in acute diseases including AKI. We examined plasma levels of three adipokines (resistin, leptin, and adiponectin) in acute PUUV infection and their associations with disease severity. Methods This study included 79 patients hospitalized due to acute PUUV infection. Plasma resistin, leptin, adiponectin, as well as IL-6 and CRP, were measured at the acute phase, recovery phase and one year after hospitalization. Results Plasma resistin levels were significantly higher in the acute phase compared to the recovery phase and one year after (median resistin 28 pg/mL (11-107) vs. 17 pg/mL (7-36) vs. 14 pg/mL (7-31), p<0.001). Maximum resistin concentration correlated with maximum plasma creatinine levels (r = 0.63; p<0.001). The higher the amount of albuminuria in the urine dipstick test (0-1+, 2+ or 3+) at admission, the higher the median of maximum resistin (24.7 pg/mL, 25.4 pg/mL and 39.6 pg/mL, respectively, p = 0.002). High resistin was also an independent risk factor for severe AKI (creatinine ≥353.6μmol/L) (OR 1.08, 95% CI 1.02-1.14). Neither plasma leptin nor adiponectin level had any correlation with creatinine concentration or the amount of albuminuria. Conclusions Plasma resistin independently associates with the severity of AKI in acute PUUV infection. The association of resistin with the amount of albuminuria suggests that the level of plasma resistin is not only influenced by renal clearance but could have some role in the pathogenesis of AKI during PUUV infection.